2006
DOI: 10.1155/idog/2006/23125
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Parasitic Infections Among Pregnant Women in Venezuela

Abstract: Introduction. Intestinal parasitic infections, especially due to helminths, increase anemia in pregnant women. The results of this are low pregnancy weight gain and IUGR, followed by LBW, with its associated greater risks of infection and higher perinatal mortality rates. For these reasons, in the setting of no large previous studies in Venezuela about this problem, a national multicentric study was conducted. Methods. Pregnant women from nine states were studied, a prenatal evaluation with a coproparasitolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
85
12
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(113 citation statements)
references
References 15 publications
(19 reference statements)
13
85
12
3
Order By: Relevance
“…In a study in Ghana (Fuseini et al 2010), 23.0% of mothers, who had mild anemia (mean Hb010.02), were infected with one or two of the following helminths: Schistosoma mansoni (12.3%), Ascaris lumbricoides (0.7%), hookworm (7%), Strongyloides stercoralis (2.3%) and Trichostrongylus (0.7%). Another study in Venezuela (Rodríguez-Morales et al 2006) showed a significant risk for anemia in those women with intestinal parasitosis (73.9%); namely A. lumbricoides (57.0%), Trichuris trichiura (36.0%), Giardia lamblia (14.1%), Entamoeba histolytica (12.0%), Necator americanus (8.1%), Enterobius vermicularis (6.3%), and S. stercoralis (3.3%). Also, a study performed by Weigel et al (1996), on the lower class urban Ecuadorian population, showed decreased maternal serum Hb, hematocrit levels, and IDA in cases of chronic intestinal parasitic infection Although evidence from the current work and others showed an association between Blastocystis infection and IDA, the causal mechanism responsible remains to be elucidated.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a study in Ghana (Fuseini et al 2010), 23.0% of mothers, who had mild anemia (mean Hb010.02), were infected with one or two of the following helminths: Schistosoma mansoni (12.3%), Ascaris lumbricoides (0.7%), hookworm (7%), Strongyloides stercoralis (2.3%) and Trichostrongylus (0.7%). Another study in Venezuela (Rodríguez-Morales et al 2006) showed a significant risk for anemia in those women with intestinal parasitosis (73.9%); namely A. lumbricoides (57.0%), Trichuris trichiura (36.0%), Giardia lamblia (14.1%), Entamoeba histolytica (12.0%), Necator americanus (8.1%), Enterobius vermicularis (6.3%), and S. stercoralis (3.3%). Also, a study performed by Weigel et al (1996), on the lower class urban Ecuadorian population, showed decreased maternal serum Hb, hematocrit levels, and IDA in cases of chronic intestinal parasitic infection Although evidence from the current work and others showed an association between Blastocystis infection and IDA, the causal mechanism responsible remains to be elucidated.…”
Section: Discussionmentioning
confidence: 97%
“…The most common cause of anemia in pregnancy worldwide is iron deficiency (Broek and Letsky 2000;Nyuke and Letsky 2000). In fact, iron losses due to various parasitic infections were reported to increase anemia in pregnant women (Dreyfuss et al 2000;Rodríguez-Morales et al 2006;Ayoya et al 2006;Fuseini et al 2010). Pregnant women are particularly vulnerable to develop IDA (Ansari et al 2009) because iron needs during pregnancy are very high; three to four times the iron needs of non-pregnant women, to meet the requirements for the fetus, placenta, and maternal red cell expansion (Hallberg 1988;Zavaleta et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In this clinical study pregnant women (n= 1038 ) from nine states were included and evaluated and the prevalence of intestinal parasitosis was evidenced in 73.9%: A lumbricoides 57.0%, T trichiura 36.0%, G lamblia 14.1%, E hystolitica 12.0%, N americanus 8.1%, E vermicularis 6.3%, S stercoralis 3.3%. Relative risk for anemia in those women with intestinal parasitosis was 2.56 (P <0.01) 76 . One cross-sectional community based study conducted on pregnant women (n=388) living in three districts around Gilgel Gibe Dam area, southwestern Ethiopia showed that, those pregnant women who had a habit of walking bare foot had high anemia prevalence (57.8%).…”
Section: Hookworm Infectionmentioning
confidence: 95%
“…Some of the common intestinal parasites such as Entamoeba histolytica, Giardia lamblia, Ascaris lumbricoides (round worm), Ancylostoma duodenale (hook worm), Trichuris trichiura (whip worm) and Enterobius vermicularis are responsible for considerable morbidity in young and adult population (Koneman et al 1997). Most of the population chronically affected with these intestinal parasites and are responsible to increased risk for iron-deficiency anaemia, nutritional anaemia, proteinenergy malnutrition, growth deficits in children, low pregnancy weight gain and intrauterine growth retardation followed by low birth weight (Stephenson 1994;Sackey et al 2003;Rodriguez-Morales et al 2006).…”
Section: Introductionmentioning
confidence: 99%